Energy never dies : Afro-optimism and creativity in Chicago - Contreras, Ayana, 1981- (Urbana : University of Illinois Press, 2021)
"From Afro Sheen to Theaster Gates and from Soul Train to Chance the Rapper, Black Chicago draws sustenance from a culture rooted in self-determination, aspiration, and hustle. In Energy Never Dies, Ayana Contreras embarks on a journey to share the implausible success stories and breathtaking achievements of Black Chicago's artists and entrepreneurs. Past and present generations speak with one another, maintaining a vital connection to a beautiful narrative of Black triumph and empowerment that still inspires creativity and pride. Contreras weaves a hidden history from these true stories and the magic released by undervalued cultural artifacts. As she does, the idea that the improbable is always possible emerges as an indestructible Afro-Optimism that binds a people together. Passionate and enlightening, Energy Never Dies uses the power of storytelling to show how optimism and courage fuel the dreams of Black Chicago"--
Preface: The verge of spring : optimism in black Chicago -- On Stony Island Avenue : boulevard of black culture -- Sort of a dream : the southern sensibility and flow of Chicago's West Side -- Found : grooves ghostly white -- Stax Fax : black Christmas begat a black love procession -- All this talk about freedom : art, soul and the Blackstone Rangers -- It's a Tom Tom, part 1 : tamales, barbecue, and 45s -- It's a Tom Tom, part 2 : iron sharpening iron -- Visions of soul : Afro Sheen, Soul Train, and black Chicago's close-up -- Brand-new you : makeover, mind over -- The coiling feedback loop of time.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 30, 2021).
JSTOR
Keywords: African Americans -- Illinois -- Chicago -- Music -- History and criticism; Popular music -- Illinois -- Chicago -- Music -- History and criticism; African Americans -- Illinois -- Chicago -- Social life and customs; African Americans -- Illinois -- Chicago -- Attitudes; Musique populaire -- Illinois -- Chicago -- Musique -- Histoire et critique; Noirs américains -- Illinois -- Chicago -- Mœurs et coutumes; Noirs américains -- Illinois -- Chicago -- Attitudes; SOCIAL SCIENCE / General; African Americans -- Attitudes; African Americans -- Music; African Americans -- Social life and customs; Popular music -- Music; Illinois -- Chicago; Criticism, interpretation, etc